ANALISIS KARAKTERISTIK REMAJA TERHADAP PERILAKU-PERILAKU BERISIKO KESEHATAN (Jurusan Ilmu Kesehatan Masyarakat, Fakultas Ilmu Keolahragaan, Universitas Negeri Semarang, Indonesia, 2022)
Adolescents during the transition of children to labile adults tend to make decisions without thinking about long-term impacts. The wrong behavior decision taken, the risky health occured. The purpose of this study was to analyze the relationship of risky health behaviors which included risky dating, smoking, alcohol and drugs consumption. This was an explanatory research with cross sectional approach involving 100 adolescents aged 15-24 years who were randomly selected in two villages in Demak. Data is collected by interview and analyzed by univariate, Chi-Square and logistic regression. Sex, mother income and self-esteem are variables that determine the occurrence of a combination of risk behavior. One third of adult smoke and date, but no one claims to have done petting and intercourse. Only 2% had drunk for alcohol, but none claimed to be drug users. There is a statistically robust relationship between smoking and dating behavior, and alcohol use with smoking. This study suggests improving life skills in adolescents in early age in order to prevent risky health behaviors.